Use of the SWOT Analysis for Evaluation of the Tourist Potential of Olsztyn Sub-Region in Warmińsko-Mazurskie Voivodship - Szmyt, Monika; Witkowska-Dąbrowska, Mirosława (Olsztyn Economic Journal, 2013)
Evaluation of the tourist potential of Olsztyn sub-region in Warmińsko-Mazurskie voivodship using the SWOT analysis was the aim of the work. The tourist potential was evaluated based on two groups of variables concerning the structural and functional resources conditioning tourist development. The studies showed that the woodiness was the major strength of the Olsztyn sub-region tourist potential. It was followed by investments in environment protection and municipal infrastructure. The major threats to tourist development in Olsztyn sub-region were the decrease in volumes of the German sentimental tourism and increasing demands of tourists concerning quality coupled with insufficient status of tourist facilities.